2014
DOI: 10.3389/fgene.2014.00144
|View full text |Cite
|
Sign up to set email alerts
|

Methylated nucleosides in tRNA and tRNA methyltransferases

Abstract: To date, more than 90 modified nucleosides have been found in tRNA and the biosynthetic pathways of the majority of tRNA modifications include a methylation step(s). Recent studies of the biosynthetic pathways have demonstrated that the availability of methyl group donors for the methylation in tRNA is important for correct and efficient protein synthesis. In this review, I focus on the methylated nucleosides and tRNA methyltransferases. The primary functions of tRNA methylations are linked to the different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
156
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(160 citation statements)
references
References 282 publications
(285 reference statements)
3
156
1
Order By: Relevance
“…Moreover, it was reported that radical SAM enzymes function in tRNA modification (Pierrel et al, 2004;Hernández et al, 2007). The methylation of tRNA is important for correct and efficient protein synthesis (Hori, 2014). It was suggested that tRNA is the only RNA methylated in pollen tubes (Steffensen, 1971) Here, we present evidence that MAT3, a SAMS expressed in pollen, plays an important role during pollen germination and pollen tube growth.…”
mentioning
confidence: 53%
“…Moreover, it was reported that radical SAM enzymes function in tRNA modification (Pierrel et al, 2004;Hernández et al, 2007). The methylation of tRNA is important for correct and efficient protein synthesis (Hori, 2014). It was suggested that tRNA is the only RNA methylated in pollen tubes (Steffensen, 1971) Here, we present evidence that MAT3, a SAMS expressed in pollen, plays an important role during pollen germination and pollen tube growth.…”
mentioning
confidence: 53%
“…The large majority of rRNA modifications are already installed co‐transcriptionally by small nucleolar (sno)RNPs, and only few base modifications require the action of lone‐standing enzymes (Watkins & Bohnsack, 2012; Sharma & Lafontaine, 2015). tRNAs contain the largest variety of nucleoside modifications, and many of them are suggested to affect tRNA biogenesis and nuclear export, tRNA structure, interaction with aminoacyl‐tRNA‐sythetases or codon recognition during translation (Agris et al , 2007; Leisegang et al , 2012; Hori, 2014; Duechler et al , 2016; Ranjan & Rodnina, 2016). Many tRNAs contain base modifications of the nucleoside at position 34 of the tRNA anticodon (the “wobble position”).…”
Section: Introductionmentioning
confidence: 99%
“…The most heavily modified types of RNA are transfer (tRNAs) and ribosomal RNAs (rRNAs). The majority of rRNA modifications are introduced cotranscriptionally by small nucleolar RNA-protein particles (snoRNPs) (Watkins and Bohnsack 2012), while modifications in tRNAs occur post-transcriptionally and are mainly mediated by lonestanding enzymes (Motorin and Helm 2011;Hopper 2013;Hori 2014). tRNA genes are transcribed by polymerase III as precursor molecules (pre-tRNA) that undergo end processing and numerous modification steps to mature.…”
Section: Introductionmentioning
confidence: 99%